Measuring the Real Size of the World Economy : The Framework, Methodology, and Results of the International Comparison Program—ICP - World Bank (Washington, DC, 2013)
This book is the most comprehensive accounting ever presented by the International Comparison Program (ICP) of the theory and methods underlying the estimation of purchasing power parities (PPPs). PPPs reveal the relative sizes of economies by converting their gross domestic products and related measurements into a common currency, thereby enabling comparisons based on economic and statistical theory.